Basal Cell Carcinoma: A Single-Center Experience. (22nd December 2012) - Abbas, Ozan Luay; Borman, Huseyin
Abstract : Background . Basal cell carcinoma comprises the vast majority of skin cancers. It predominantly affects fair-skinned individuals, and its incidence is rising rapidly. Etiology may be multifactorial, but sun exposure appears to play a critical role. When detected early, the prognosis is excellent. Thus appropriate diagnosis, treatment, and surveillance are of utmost importance. Methods . From January 1994 to May 2012, 518 basal cell carcinomas were excised in our clinic. Data were collected retrospectively. Results . During 18-year period, 518 BCCs were excised from 486 patients. Most of the patients were males with a median age of 65.6 years. Most of the basal cell carcinomas were located in the head region. Nodular histological subtype dominated our series. Six percent of the excised lesions required reexcision because of involved margins. Our recurrence rate was 6.94% with the nose and the periauricular and periocular regions being the most common sites of occurrence. Conclusion . Although there is relatively low attributable mortality, the morbidity and cost of treatment are significant. A large body of information serves as a foundation for oncologic principles, diagnosis methods, surgical excisions, follow-up protocols, and reconstructive methodologies that are currently in use. Surgical ablation remains the mainstay of treatment.